Exigências nutricionais de caprinos da raça alpina em crescimento. 2. composição corporal e do ganho em peso em proteína, extrato etéreo, energia, cálcio e fósforo - Sousa, HMH; de Queiroz, A. C.; Resende, Kleber Tomás de [UNESP]; da Silva, JFC; Pereira, J. C.; de Gouveia, L. J. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1998)
This experiment was conducted to estimate the body composition and the composition of the weight gain of energy, protein, calcium and phosphorus of kid goals in the growing phase. Fifteen four-month-old male kid goats, average live weight of 20 kg and fed an isocaloric and isoproteic diet with an increased level of calcium, were used. The experimental period was 27 days. The animals were slaughtered to determine the body composition and estimate the body content of energy, protein, ether extract, calcium, and phosphorus. The average values for the body composition were, respectively: water, 64.88%; protein, 15.22%; ether extract 14.17%; energy, 2.40 Mcal/kg as fed; calcium, .79%; and phosphorus, .54%. The values for the composition of live weight gain for 18 and 26 kg of live weight were: protein, 168.15 and 183.12 g; ether extract 83.47 and 67.71 g; energy, 1.80 and 1.63 Mcal/kg as fed; calcium, 6995.36 and 6579.02 mg; and phosphorus, 5860.95 and 6427.16 mg, respectively.
Nutritional requirements of Alpina breed goats in the growing phase. 2. Body composition and of the weight gain for protein, ether extract, energy, calcium, and phosphorus
Keywords: calcium; goats; body content; growth; energy; Phosphorus; fat; protein